Post liver transplant tuberculosis - Rodrigues, Luis Vaz (BMJ Publishing Group, 2009)
We report on a patient diagnosed with disseminated (hepatic and pulmonary) tuberculosis in the context of immunosuppression following liver transplant. During the administration of anti-tuberculosis drugs an abrupt elevation of liver enzymes was detected leading us to suspect drug toxicity rather than graft rejection. Nevertheless, careful surveillance and adjustment of serum levels of immunosuppressant drugs permitted continuance of tuberculosis treatment with no further side effects.